Temporal evolution of seismic fragility curves for concrete box-girder bridges in California. (15th August 2015) - Ramanathan, Karthik; Padgett, Jamie E.; DesRoches, Reginald
Highlights: The evolution in design details for Californian box-girder bridges is captured. The importance of design details on the fragility of box-girder bridges is quantified. The framework for fragility analyses considers multiple component vulnerability. Seismic vulnerability reduces with evolution of column design philosophy. Pre 1971 era bridges with multi column bents and seat abutments are most vulnerable. Abstract: Fragility analyses is a powerful tool for the seismic risk assessment of highway bridges. Multispan continuous concrete box-girder bridges account for the bulk of the California bridge inventory. Although several studies have looked at the seismic response and fragility of individual box-girder bridges, very little research has explored the fragility of the box-girder bridge class holistically. Exacerbating this situation is the lack of considerations of design details unique to the era in which the bridges were designed and constructed, in their fragility development. This paper addresses this gap by investigating the influence of evolution of seismic design principles and details on the seismic performance of multispan continuous concrete box-girder bridge class, as well as the failure probability through the development of fragility curves across three design eras demarcated by the 1971 San Fernando and 1989 Loma Prieta earthquakes. Detailed nonlinear analytical models capturing the bridge characteristics within a design era are developed and nonlinear time history analysis is employed to develop analytical fragility curves. Significant improvement in performance is seen in modern bridges designed according to capacity design principles.